Building on ASEAN's Success : Towards an Asia Pacific Community - Rudd, Kevin, 1957- (Book collections on Project MUSE., 2008)
This book contains the text of the 29th Singapore Lecture delivered by the Honourable Kevin Rudd, Prime Minister of Australia, on 12 August 2008. ...